I’m Not Givin’ Up: Predictors Of Academic Resilience Among College Students - Vitaloka, Lela; Setiawati, Farida Agus (LPPM Universitas 17 Agustus 1945 Samarinda, 2025)
This research is motivated by the phenomenon of academic pressure felt by students. The process of higher education often causes academic pressure on students, especially when completing lecture assignments that are quite heavy which can cause academic procrastination behavior. This study aims to determine the influence of self-control and self-compassion on academic resilience. Academic resilience is defined as the resilience of students when faced with situations of academic pressure. The research method uses quantitative research with multiple linear regression analysis techniques. The participants of this study amounted to 420 students. The results showed that there was an effect of self-control and self-compassion together on academic resilience in students with a significance value of 0.000 (p<0.05). Therefore, it can be concluded that there is an effect of self-control and self-compassion research on academic resilience to students. The implications of the study show the importance of being open to understanding difficult situations with adaptive abilities that foster academic resilience.